Predicting higher education graduation rates from institutional characteristics and resource allocation - Hamrick, Florence A.; Schuh, John H.; Shelley, Mack C. (Education Policy Analysis Archives, 2004)
This study incorporated institutional characteristics (e.g., Carnegie type, selectivity) and resource allocations (e.g., instructional expenditures, student affairs expenditures) into a statistical model to predict undergraduate graduation rates. Instructional expenditures, library expenditures, and a number of institutional classification variables were significant predictors of graduation rates. Based on these results, recommendations as well as warranted cautions are included about allocating academic financial resources to optimize graduation rates